Design and development of a precision flow perturbation device - Arwinder Singh. (2013)
This project entailed the design of a perturbation device which would disturb a free jet at a prescribed amplitude and frequency that can be altered using the device. The device was designed with the idea of a piston-crank mechanism in mind where a link can be connected at increasing radii of the disc in order to increase the displacement of the piston and the frequency of the perturbation. This device was then designed using Solidworks along with the stand for the motor so that it can be kept at an elevated level with respect to the pipe on which perturbation will be carried out.